1st Libyan Conference for Science and Technology - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2021)
1st Libyan Conference for Science and Technology will be held at Tripoli National University on June 12, 2021 in Janzour, Libya. The conference aims to encourage the meeting and gathering of academics and innovative experts in various scientific fields who are united by the basics and applications of technology.